Proceedings of the 19th Annual International Conference on Digital Government Research: Governance in the Data Age 2018
DOI: 10.1145/3209281.3209305
|View full text |Cite
|
Sign up to set email alerts
|

Citizen engagement in an open election data initiative

Abstract: Citizen engagement is key to the successful and sustainable use of Open Government Data (OGD), involving multiple activities ranging from the retrieval and conversion of raw data to OGD based applications, to the use of these applications to solve societal problems. However, there is a lack of insight into what drives citizens to engage in OGD initiatives. Such insight helps inform policymakers in stimulating and improving the engage ability of an OGD program. This study aims to identify factors that influence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 30 publications
0
22
0
Order By: Relevance
“…Mata Massa is an application that was launched by Aliansi Jurnalis Independen (AJI) or Independent Journalists Alliance and ICT Laboratory for Social Changes (iLab) in November 2013. This application receives reports of election violations such as money politics through mobile phone [15]. Mata Massa deployed 200 volunteers to organize the reports submitted by the citizens through their devices [14].…”
Section: A the Development Of Participatory Election Monitoring In Imentioning
confidence: 99%
See 2 more Smart Citations
“…Mata Massa is an application that was launched by Aliansi Jurnalis Independen (AJI) or Independent Journalists Alliance and ICT Laboratory for Social Changes (iLab) in November 2013. This application receives reports of election violations such as money politics through mobile phone [15]. Mata Massa deployed 200 volunteers to organize the reports submitted by the citizens through their devices [14].…”
Section: A the Development Of Participatory Election Monitoring In Imentioning
confidence: 99%
“…According to Purwanto, Jansenn and Zuiderwijk [15], Kawal Pemilu faced a challenge in recruiting volunteers to digitise 478,829 C1 forms. In order to solve this problem, Ainun chose to adopt Multi-Level Marketing recruitment by recruiting ten friends as "downline" who then recruited another ten and so forth, through a secret Facebook group [15]. This method enabled him to gather 700 volunteers in only one day after he set up this platform [15].…”
Section: A the Development Of Participatory Election Monitoring In Imentioning
confidence: 99%
See 1 more Smart Citation
“…We include six publications which are deemed relevant for this study (see Table 3). Based on the selected papers, we observed that many factors influence citizens to engage with OGD or to engage in an open data hackathon: intrinsic motivations such as fun and enjoyment and intellectual challenge [12]; extrinsic motivations concerning performance expectancy [13] or relative advantage [16], learning and developing skills, and networking [11,12]; effort expectancy [13] related to ease of use [17]; social influence [13,18] including contributing to societal benefits [11,18]; and data quality [18].…”
Section: A Framework For Analyzing Citizens' Motivations To Engage Inmentioning
confidence: 99%
“…Purwanto, Zuiderwijk and Janssen [18] A participant's effort expectancy is related to the degree of ease associated with the use of open data and technology for solving a hackathon's challenge. It also concerns the participant's perceived capabilities/skills required for creating solutions which reciprocally affects the perceived ease of use.…”
Section: Accuracymentioning
confidence: 99%